Low reversed cyclic loading tests for integrated precast structure of lightweight wall with single-row reinforcement under a lightweight steel frame. Issue 10 (3rd October 2018) - Suizi, Jia; Wanlin, Cao; Yuchen, Zhang
Abstract : Given the development of precast structures for low-rise residential buildings, this study explores a new structure—namely, an integrated precast structure of lightweight recycled concrete wall with single-row reinforcement—under a lightweight steel frame filled with recycled concrete (integrated precast structure for short). The lightweight steel frame and lightweight wall cooperate to bear the forces. The applied concealed bracing, either a rebar bracing or a steel plate bracing, increases the shear resistance of the wall. The lightweight steel frame is designed to bear the vertical loading, whereas the seismic load in the horizontal direction is jointly borne by the frame and wall. This study presents the results of low reversed cyclic loading tests on nine specimens of integrated precast structures. An analysis is then carried out to investigate the mechanical properties of the specimens; based on these results, a formula for the force-bearing performance of the inclined section is developed. The results show satisfactory performance as an integrated piece; the proposed structure has two seismic lines of defence, with the lightweight wall restraint by the side frame being the first line and the steel frame being the second line. Because the failure of the wall can be categorized as shear failure, the restraint of the lightweight steel frame significantly reduces the potential damage of the wall. As the beams and columns of the steel frame tend to bend against failure, the wall filling helps resist sliding. Therefore, the reinforced joints of the connecting beams and columns show no visible signs of damage, indicating that the connection between the beams and columns is reliable. The narrow spacing of rebars and the setting of concealed bracing contribute to the increase in ductility and energy efficiency of the integrated structure and the evident reduction in the failure process. Furthermore, the recycled concrete increases the seismic resistance of the structure.